Implementasi Algorithma Crochemore-Perrin Pada Aplikasi Pengenalan Mata Uang Negara Di Dunia Berbasis Mobile - Windi Suhardi (JURIKOM (Jurnal Riset Komputer), 2021)
Money is anything that can be accepted by the general public as a medium of exchange in economic traffic. In general money is used as a means of payment for the purchase of goods and services and other valuable assets even for the payment of debts. Countries in the world have a very large number, each country in the world each has a different currency based on a predetermined unity. The problem that often occurs in the general public about the currencies of countries in the world is the difficulty to find information on names the currencies of countries in the world in a fast and precise time. To overcome the above problems, the author builds an application for introducing currency in a mobile-based world by applying the Crochemore-Perrin algorithm to minimize the time needed in the process of finding information about the currencies of each country in the world. The application of the introduction of state currencies in the world based on mobile in this study can be used offline or online and has a display of user experience or interaction that is more convenient and enjoyable so that it can be used easily anywhere and anytime by the general public to find information about the country's currency in the world. The Crochemore-Perrin algorithm is a string matching algorithm published by Maxime Crochemore and Dominique Perrin in 1991. This algorithm factifies the pattern into two parts. The matching phase of this algorithm consists of two parts, first matching the right pattern character from left to right, then matching the left pattern pattern from right to left.Keywords: Introduction to Currency, String Matching, Crochemore-Perrin, Mobile.